EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Nadia Nadia; Achmadi Achmadi; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aimed to find out the effectiveness of the implementation of STAD type cooperative learning models to improve students' learning outcomes in social sciences subjects. The form of the research was pre-experimental design using one group pretest-post-test design. The subjects of the study were class VII E students at SMP Negeri 4 Sungai Raya Kabupaten Kubu Raya which numbered 26 people. The data collection techniques used in this study were direct observation, measurement and documentary study techniques. Data collection tools were observation sheet or check list, record sheet and the results taken form of pre-test and post-test. Based on data analysis, the normality test results state that the residual value is distributed normally with a significant value of 0.621>0.05. Moreover, the hypothetical test results stated that Ho was rejected and Ha accepted based on sig (2-tailed) values pre-test and post-test results with a value of 0.000 means smaller than 0.05. According to effect size calculation, the result obtained was 2.13 which kategorized as high, means that STAD type cooperative learning model has a big influence in improving the learning outcome of students in social sciense subjects grade VII E in SMP Negeri 4 Sungai Raya Kabupaten Kubu Raya. Keywords: Learning Outcomes, STAD Type Cooperative Model